TRANSFORMASI HIJAU DI PESISIR SURABAYA: PENERAPAN TEKNOLOGI CERDAS DALAM PERTANIAN PERKOTAAN UNTUK PEMBERDAYAAN MASYARAKAT - Edi Sasongko, Purnomo; Fari Aditya , Haidar; Mahendra Kusuma, Ramadhani; Supriadi, Yudi Nur (Batara Wisnu : Indonesian Journal of Community Services, 2024)
Coastal environmental management is a major challenge in urban areas such as Surabaya which are facing the pressures of urbanization and climate change. This article discusses the implementation of smart technologies in urban agriculture as part of the green transformation to empower coastal communities. This community service activity includes the application of hydroponic and verticulture farming systems supported by Internet of Things (IoT)-based technology to monitor the plant growing environment. In addition to increasing crop yields, this technology helps communities manage resources efficiently, such as water and nutrients. Intensive training and mentoring are provided to increase community capacity in utilizing technology and developing agricultural product-based entrepreneurship. The results of the program show an increase in household income, environmental awareness, and sustainability of coastal ecosystems. This article offers a technology-based empowerment model that can be replicated in other coastal areas, contributing to the sustainable development goals (SDGs).